Phonology Analysis Theory of Phonetics - Namira Syaharani; Syahwan Hamdany; Yani Lubis (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2023)
Phonetic features such as phonemes, minimal pairs, suspicious pairs, and procedures are applied in this study. Identifies the analyzed phoneme, interview methods, native speaker involment and methods. Literature studies are for data collection, data analysis, and especially during analysis. Phonemes are completed through multiple processes including preprocessing (pre-process), separation process, merger process (separation procedure).